CHARACTERIZATION OF Co(II)-PAMAM DENDRIMER COMPLEXES WITH POLYPROPYLENE OXIDE CORE BY USING UV-VIS SPECTROSCOPY - Erturk, Ali Serol; Gurbuz, Mustafa Ulvi; Tulu, Metin; Bozdogan, Abdurrezzak Emin (SOC CHEMISTS TECHNOLOGISTS MADECONIA, 2016)
The aim of this study was to characterize poly(amidoamine) (PAMAM) dendrimer complexes of Co(II) ions by using UV-Vis spectroscopy. For this aim, a generation-4 polypropylene oxide (Jeffamine T-403) cored and amine-terminated PAMAM dendrimer (P-4) was used as a model complexation agent. Optimum complexation condition for P-4 was determined by potentiometric and spectroscopic titration studies. Extent of protonation (EOP) of the amino groups of P-4 was determined from the potentiometric titration data and validated with spectroscopic titration data. The results indicated that pH 8 was the optimum dendrimer aqueous solution media, where the available number of tertiary amines present in P-4 was the highest for possible metal complexation. At the optimized conditions, UV-Vis characterization of the Co(II)-P-4 complexes was performed and 585-635 nm d-d transition bands were observed as the characteristic complexation bands of the tertiary amine groups of P-4 with Co(II) ions. Obtained Co(II)-P-4 complexes might be considered for the development of magnetic resonance image (MRI) improvers or MRI contrast agents.
Keywords: PAMAM dendrimer; Jeffamine; complexation; UV-Vis spectroscopy; MRI contrast agents; MICROWAVE-ASSISTED SYNTHESIS; POLY(AMIDOAMINE) DENDRIMERS; BINDING; PROTONATION; ION; Chemistry; Engineering